The Star, 16 Jun 2008 - C.S Ntahan (Star Publications (Malaysia) Berhad, 2008)
The abandoned police quarters in Jalan Rasah, Seremban, is not only attracting unwelcome visitors but has turned into an eyesore to those living in nearby residential areas.